In Vitro Maturation of Cumulus-Oocyte Complexes for Efficient Isolation of Oocytes from Outbred Deer Mice - Choi, Jung Kyu (Public Library of Science, 2013)
BACKGROUND: The outbred (as with humans) deer mice have been a useful animal model of research on human behavior and biology including that of the reproductive system. One of the major challenges in using this species is that the yield of oocyte isolation via superovulation is dismal according to the literature to date less than ∼5 oocytes per animal can be obtained so far. OBJECTIVE: The goal of this study is to improve the yield of oocyte isolation from outbred deer mice close to that of most laboratory mice by in vitro maturation (IVM) of cumulus-oocyte complexes (COCs). METHODS: Oocytes were isolated by both superovulation and IVM. For the latter, COCs were obtained by follicular puncture of antral follicles in both the surface and inner cortical layers of ovaries. Immature oocytes in the COCs were then cultured in vitro under optimized conditions to obtain metaphase II (MII) oocytes. Quality of the oocytes from IVM and superovulation was tested by in vitro fertilization (IVF) and embryo development. RESULTS: Less than ∼5 oocytes per animal could be isolated by superovulation only. However, we successfully obtained 20.3±2.9 oocytes per animal by IVM (16.0±2.5) and superovulation (4.3±1.3) in this study. Moreover, IVF and embryo development studies suggest that IVM oocytes have even better quality than that from superovulation The latter never developed to beyond 2-cell stage as usual while 9% of the former developed to 4-cells. SIGNIFICANCE: We have successfully established the protocol for isolating oocytes from deer mice with high yield by IVM. Moreover, this is the first ever success to develop in vitro fertilized deer mice oocytes beyond the 2-cell stage in vitro. Therefore, this study is of significance to the use of deer mice for reproductive biology research.